Knowledge Level of the Primary Healthcare Providers on Chronic Obstructive Pulmonary Disease and Pulmonary Rehabilitation - Tuğba Göktalay; Ayşe Nur Tuncal; Seçil Sarı; Galip Köroğlu; Yavuz Havlucu; Arzu Yorgancıoğlu (Pulmonary Medicine)
Introduction. Awareness of the healthcare providers on chronic obstructive pulmonary disease (COPD), which is an important cause of mortality and morbidity in our country and all over the world, and on pulmonary rehabilitation (PR) which plays an important role in its nonpharmacological treatment will provide effectiveness in diagnosis and treatment of COPD. The present study aimed at determining knowledge level of the healthcare providers about COPD and PR. Materials and Methods. In this cross-sectional study, family practitioners and staff of home-care in central county of Manisa City were applied a questionnaire in order to determine their knowledge level on COPD and pulmonary rehabilitation during the in-service training on “pulmonary rehabilitation, home-care services for the pulmonary diseases, and respiratory exercises.” Results. 65.5% of the healthcare providers responded to the survey. Rate of those correctly knowing at least one of four items was 97.2%. No responder knew all items correctly. Average value for correct answers was 5.30 ± 2.1 (range: 1–10). The physicians, men, and those working in family health centers had higher level of knowledge on COPD compared to nonphysician healthcare providers (p=0.006), women (p=0.002), and those working in other practices (p=0.019), respectively. Conclusion. Knowledge level of the primary healthcare providers on COPD and PR remains inadequate. Dynamic postgraduate training on this topic will be useful in referring the patients to centers giving service for this condition.